Assessing and measuring environmental impact and sustainability - Klemes, Jiri Jaromir (Butterworth-Heinemann, 2015)
Assessing and Measuring Environmental Impact and Sustainability answers the question "what are the available methodologies to assess the environmental sustainability of a product, system or process? Multiple well-known authors share their expertise in order to give a broad perspective of this issue from a chemical and environmental engineering perspective. This mathematical, quantitative book includes many case studies to assist with the practical application of environmental and sustainability methods. Readers learn how to efficiently assess and use these methods. This book summarizes all relevant environmental methodologies to assess the sustainability of a product and tools, in order to develop more green products or processes. With life cycle assessment as its main methodology, this book speaks to engineers interested in environmental impact and sustainability